MTA in the treatment of furcation perforation in upper molar under operative microscopy: case report - Macedo, Isabella Figueiredo Assis (2022)
During endodontic procedures, the occurrence of iatrogenesis can compromise the success of the treatment and knowing how to conduct them is essential for a favorable outcome. Endodontic perforation is a communication between the pulp space and the external surface of the tooth. The most suitable material for sealing perforations is Mineral Trioxide Aggregate (MTA), a bioceramic capable of inducing the formation of mineralized tissue. The use of loupes or operating microscope is an important tool in the management of complex cases, as it allows magnification and illumination of the operating field. The objective of this study is to report a case of a patient submitted to endodontic treatment and sealing of furcation perforation, with the aid of operative microscopy, evidencing the use of MTA. The patient was referred to Faculdade São Leopoldo Mandic for endodontic treatment of tooth 26, which included sealing a perforation and locating the mesiobuccal canal. Chemical-mechanical preparation of root canals was performed with ProDesign Logic instruments, 2% chlorhexidine gel, and distilled water as irrigant. The sealing of the perforation was performed with MTA Angelus. After a period of three months, the patient remained asymptomatic. It was concluded that the treatment was satisfactorily completed, considering the complexity of the case, influenced by patient's age, the difficult access and direct visualization of the tooth and the presence of complications. The use of an operating microscope provided field magnification and illumination, necessary for the detection of the mesiobuccal canal and greater accuracy in the application of the repair material.